1999
DOI: 10.1002/(sici)1099-1263(199911/12)19:6<437::aid-jat600>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Chromium status of tannery workers in relation to metabolic disorders

Abstract: Chromium (Cr), being an excellent tanning agent, is widely used in the leather industry. In the process of leather production, tannery workers are exposed to either inorganic Cr(III) compounds or Cr bound to proteins (leather dust). The total Cr content in tannery air (1–54 μg m−3) is rather high in comparison to ambient air (4–6 ng m−3) but the amount of Cr in inhalable particles (<10 μm) is two to three orders of magnitude less (20–60 ng m−3). The total daily intake of Cr was estimated by the analysis of die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Workers employed in leather tanning companies may be exposed to higher-than-normal levels of chromium, mostly trivalent chromium (Cr(III)) ( Life Systems Inc et al , 2008 ), either in the form of inorganic Cr(III) compounds or as Cr bound to protein (leather dust) ( Stupar et al , 1999 ). Toxicity for Cr(III) is very low, even when present in very large quantities, while hexavalent chromium (Cr(VI)) has been found to be biologically active.…”
Section: Workers In Footwear and Tannery Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Workers employed in leather tanning companies may be exposed to higher-than-normal levels of chromium, mostly trivalent chromium (Cr(III)) ( Life Systems Inc et al , 2008 ), either in the form of inorganic Cr(III) compounds or as Cr bound to protein (leather dust) ( Stupar et al , 1999 ). Toxicity for Cr(III) is very low, even when present in very large quantities, while hexavalent chromium (Cr(VI)) has been found to be biologically active.…”
Section: Workers In Footwear and Tannery Industrymentioning
confidence: 99%
“…Concentrations of chromium in blood, serum, urine and hair have long been used in biological monitoring of environmentally and occupationally exposed populations, as a biomarker of exposure ( Simpson and Gibson, 1992 ; Rajaram et al , 1995 ; Grevatt and United States. Environmental Protection Agency, 1998 ; Stupar et al , 1999 ; Medeiros et al , 2003 ).…”
Section: Workers In Footwear and Tannery Industrymentioning
confidence: 99%
“…Similar findings have also been reported[11] who reported that the majority of the workers who died of pancreatic cancer had high exposure to formaldehyde and high dye and solvent exposure. High mortality form of pancreatic cancer is also shown in earlier studies[152021] showed the strong ability of proteins of leather dust to bind inorganic Cr III compound and facilitate their entrance into gastro intestinal tract.…”
Section: Introductionmentioning
confidence: 74%
“…Chromium exists in several oxidation states out of which Cr(III) and Cr(VI) are most stable. Cr(III) is toxic at higher concentration with its permissible limits of 0.05 and 0.1 mg L -1 concentration in potable and tannery effluents respectively [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%